Interaction Between Tumor-Infiltrating Lymphocytes and the PD-1/PD-L1 Pathway in Non-Small Cell Lung Cancer: Implications for Tumor Progression and Immunotherapy Response — A Systematic Review - Sultan Pasha; Rasi Sallang; Leony Octavia (MARAS : Jurnal Penelitian Multidisiplin, 2026)
Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-related mortality worldwide. The interaction between tumor-infiltrating lymphocytes (TILs) and the programmed cell death protein-1/programmed death-ligand 1 (PD-1/PD-L1) pathway plays a critical role in tumor progression and response to immunotherapy. This systematic review evaluated current evidence regarding the prognostic and predictive significance of these immune biomarkers in NSCLC. A systematic search was conducted in PubMed, SpringerLink, and ScienceDirect for studies published between 2018 and 2024. Eligible studies included original human research assessing TIL characteristics, PD-1/PD-L1 expression, and their associations with survival outcomes or responses to immune checkpoint inhibitors. Ten studies met the inclusion criteria. The findings demonstrated that high CD8⁺ TIL infiltration was consistently associated with improved survival and enhanced responsiveness to PD-1/PD-L1 blockade. PD-L1 expression was frequently linked to immune-inflamed tumor phenotypes, although its prognostic value varied across studies. Several studies reported that the combined evaluation of TILs and PD-1/PD-L1 expression provided better predictive accuracy than either biomarker alone. Furthermore, adoptive TIL therapy showed promising clinical activity in patients with PD-1-resistant disease. These findings indicate that the interaction between TILs and the PD-1/PD-L1 pathway is a key determinant of immunotherapy outcomes in NSCLC and may support more effective patient stratification and personalized treatment strategies.